COMPETITIVE PRIORITIES AND STRATEGIC ALIGNMENT AS MEDIATORS IN THE RELATIONSHIP BETWEEN COMPANIES IN THE BRAZILIAN AUTOMOTIVE SUPPLY CHAIN - Garo Junior, Wagner Roberto; Guimarães, Marcia Regina Neves (The South African Journal of Industrial Engineering, 2018)
This study aimed to assess how the search for strategic alignment and competitive priorities influences the relationship between companies in the Brazilian automotive supply chain. To achieve this, qualitative research was conducted using an integrated case study in the automotive segment of companies that had business relationships with each other. The following elements were studied: an automaker, three automotive systems suppliers, and three second-tier suppliers. The results show that there is a strategic alignment in the chain, mainly driven by the automaker and the systems suppliers, and that competitive priorities shape the forms of the relationships between companies in the automotive supply chain.